2021
DOI: 10.24115/s2446-6220202173a1395p.226-234
|View full text |Cite
|
Sign up to set email alerts
|

Social responsibility during the COVID-19 pandemic (The Republic of Bashkortostan)

Abstract: Analysis of modern prevention concepts makes it possible to single out individual-oriented preventive concepts, and concepts of socio-political orientation. Individually oriented prevention involves the use of professional assistance at the earliest stage. The consequences of a social problem or individual disturbance must be promptly counteracted, which requires knowledge about the social space and living conditions of the individual, since such knowledge provides current planning and/or strategic interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Large companies of the oil and gas sector reduce their staff numbers by about 1% per year. Rosneft is the only company to annually increase its staff through establishing new enterprises (table 2) (Gaisina et al, 2021). The sociological study results showed that 30% of the personnel of oil and gas companies belong to the category of major executives (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Large companies of the oil and gas sector reduce their staff numbers by about 1% per year. Rosneft is the only company to annually increase its staff through establishing new enterprises (table 2) (Gaisina et al, 2021). The sociological study results showed that 30% of the personnel of oil and gas companies belong to the category of major executives (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Russia is a technologically independent participant in the hydroelectric power market, actively supplies this product to neighboring countries, which creates the potential for innovative and investment growth through the Chinese market. Both technological and resource partnerships are areas of international cooperation that can replace a part of the country's hydrocarbon revenues in the event that the global economy turns away from hydrocarbons by 2050 [15][16][17][18][19][20].…”
Section: Assessment Of the Innovation And Investment Potential For Th...mentioning
confidence: 99%